Gestational inhalation of nanoparticles alters placental glucose transporter expression and increases glucose flux in rats - Talia N. Seymore; Sara Hoffmann; Pedro Louro; Carol Gardner; Michael J. Goedken; Phoebe A. Stapleton (Toxicology and Applied Pharmacology, 2026)

Polystyrene nanoplastics disrupt mouse placenta development in a sex-dependent manner - Hanin Alahmadi; Allison Harbolic; Christopher De Oliveira-Cordova; Raulle Reynolds; Michelle Jojy; Courtney Potts; Sofia Doan; Tanvi Mathur; Mohammad Saiful Islam; Melisa J. Andrade; Quinton Smith; Phoebe A. Stapleton; et al. (Reproductive Toxicology, 2026)

Erratum to ‘Gestational inhalation of nanoparticles alters placental glucose transporter expression and increases glucose flux in rats’ [Toxicol. Appl. Pharmacol. 515 (2026) 117996] - Talia N. Seymore; Sara Hoffmann; Pedro Louro; Carol Gardner; Michael J. Goedken; Phoebe A. Stapleton (Toxicology and Applied Pharmacology, 2026)

Associations of serum PFAS with COVID-19 antibody levels among fully vaccinated adults - Rachel A. Bauer; Zhao Yang; Michael Petriello; Sharon Zhang; Heather M. Stapleton; John L. Adgate; Courtney C. Carignan (Environmental Research, 2026)

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Regional Extrathoracic Deposition of Inhaled Epinephrine in an Idealized Child Airway: Influence of Pressurized Metered Dose Inhaler Actuator Orifice Diameter - Kineshta Pillay; Scott Tavernini; Conor A. Ruzycki; George H. Luciuk; Kevin W. Stapleton; Warren H. Finlay; Andrew R. Martin (Pharmaceutical Research, 2026)

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Gestational exposure to micro and nanoplastics differentially impacts cardiac development and function in male and female rats throughout the lifespan - Chelsea M. Cary; Samantha Adams; Gina M. Moreno; Talia N. Seymore; Marianne Polunas; Michael J. Goedken; Xiang Wang; Edward J. Yurkow; Phoebe A. Stapleton (Toxicology and Applied Pharmacology, 2025)

Habitat fidelity in hawksbill sea turtles - Andrew S. Maurer; Julia A. Horrocks; Claudio Bellini; Karen L. Eckert; Alexandra L. Fireman; Mariana M. P. B. Fuentes; Barry Krueger; Kathryn E. Levasseur; Maria A. Marcovaldi; Renata M. A. Ramos; Seth P. Stapleton; Hannah B. Vander Zanden; et al. (Ecology, 2025)
Climate change is altering habitat suitability and driving shifts in species distributions. To understand potential responses by mobile animals, it is essential to assess levels of plasticity in habitat use, ranging from transience to long‐term fidelity. Here, we evaluate the fidelity of hawksbill sea turtles ( Eretmochelys imbricata ) to habitats used while foraging (our primary focus), migrating, and nesting. After satellite tracking 17 adult females from three Western Atlantic nesting areas, we then re‐tracked them in a subsequent year. Of 15 turtles with sufficient data to assess interannual foraging area fidelity, 14 returned to the same home range, exhibiting overlap between successive 50% utilization distributions (UDs); the 15th individual shifted

Rapid detection of microplastics and nanoplastics in seconds by mass spectrometry - Mengyuan Xiao; Yongqing Yang; Hanin Alahmadi; Allison Harbolic; Gina M. Moreno; Terry Yu; Jerry Liu; Alex Guo; Genoa R. Warner; Phoebe A. Stapleton; Hao Chen (Journal of Hazardous Materials, 2025)

A global assessment of microplastic abundance and characteristics on marine turtle nesting beaches - Zara L.R. Botterell; Jed Ardren; Elly Dove; Ellen McArthur; David S. Addison; Oyeronke M. Adegbile; Pierre Didier Agamboue; Andrews Agyekumhene; Phil Allman; Alexandra Alterman; Adren Anderson; Theresa Arenholz; et al. (Marine Pollution Bulletin, 2025)

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Visual categorisation of images of familiar objects based on their authenticity: an fMRI study - Grace A. Gabriel; Cristina Simões-Franklin; Georgia O’Callaghan; John Stapleton; Fiona N. Newell (Experimental Brain Research, 2025)
Under most circumstances, we can rely visual information to quickly and accurately discriminate “real” objects (e.g., fresh fruit) from “fake” objects (e.g., plastic fruit). It is unclear, however, whether this distinction is made early along the ventral visual stream when basic object features such as colour (e.g., primary visual cortex; V1) and texture (e.g., collateral sulcus; COS) are being processed, or whether information regarding object authenticity is extracted in later visual or memory regions (e.g., perirhinal cortex, lateral occipital cortex). To examine this question, participants were placed in an fMRI scanner, and presented with 300 objects photographed in colour or greyscale. Half of the objects were fake, and the other half were real. The participant’s task was to categorise each image as presenting either a real or fake object. Broadly, our analyses revealed significant activation in CoS when participants categorised real objects, particularly when they were presented in colour. We also observed activation in V1 for coloured objects, particularly real ones. These results suggest that our seemingly intuitive ability to rapidly discriminate real from fake objects occurs at the early stages of visual processing, such as when the brain is extracting surface-feature information like texture (CoS) or colour (V1). Future studies could consider the time course of these neural events and probe the importance of cross-modal (e.g., audition and haptic) information underpinning feature extraction for distinguishing real from fake objects.

Identification of micro- and nanoplastic particles in postnatal sprague-dawley rat offspring after maternal inhalation exposure throughout gestation - Gina M. Moreno; Tanisha Brunson-Malone; Samantha Adams; Calla Nguyen; Talia N. Seymore; Chelsea M. Cary; Marianne Polunas; Michael J. Goedken; Phoebe A. Stapleton (Science of The Total Environment, 2024)

An international inter-laboratory study to compare digital PCR with ISO standardized qPCR assays for the detection of norovirus GI and GII in oyster tissue - Ingeborg L.A. Boxman; Ramia Molin; Sofia Persson; Anna Juréus; Claudia C.C. Jansen; Nils P. Sosef; Soizick F. Le Guyader; Joanna Ollivier; Maija Summa; Maria Hautaniemi; Elisabetta Suffredini; Simona Di Pasquale; et al. (Food Microbiology, 2024)

Long-Term Follow-Up of Cerebral Aneurysms Completely Occluded at 6 Months After Intervention with the Woven EndoBridge (WEB) Device: a Retrospective Multicenter Observational Study - Kareem El Naamani; Panagiotis Mastorakos; Nimer Adeeb; Mathews Lan; James Castiglione; Omaditya Khanna; Jose Danilo Bengzon Diestro; Rachel M. McLellan; Mahmoud Dibas; Justin E. Vranic; Assala Aslan; Hugo H. Cuellar-Saenz; et al. (Translational Stroke Research, 2024)

Correction to: The Woven EndoBridge (WEB) Device for the Treatment of Intracranial Aneurysms: Ten Years of Lessons Learned and Adjustments in Practice from the WorldWideWEB Consortium - Adam A. Dmytriw; Mahmoud Dibas; Sherief Ghozy; Nimer Adeeb; Jose Danilo Bengzon Diestro; Kevin Phan; Hugo H. Cuellar-Saenz; Ahmad Sweid; Sovann V. Lay; Adrien Guenego; Leonardo Renieri; Ali Al Balushi; et al. (Translational Stroke Research, 2023)

PFAS levels in paired drinking water and serum samples collected from an exposed community in Central North Carolina - Samantha M. Hall; Sharon Zhang; George H. Tait; Kate Hoffman; David N. Collier; Jane A. Hoppin; Heather M. Stapleton (Science of The Total Environment, 2023)

The Woven EndoBridge (WEB) Device for the Treatment of Intracranial Aneurysms: Ten Years of Lessons Learned and Adjustments in Practice from the WorldWideWEB Consortium - Adam A. Dmytriw; Mahmoud Dibas; Sherief Ghozy; Nimer Adeeb; Jose Danilo Bengzon Diestro; Kevin Phan; Hugo H. Cuellar-Saenz; Ahmad Sweid; Sovann V. Lay; Adrien Guenego; Leonardo Renieri; Ali Al Balushi; et al. (Translational Stroke Research, 2023)

School Situational Analysis Helps to Explain the Landscape for Future Nutrition Education - Emily Sklar; Rebecca H. Crosby; Cami Manning; Kristen Stapleton; Valarie Fung-A-Ling; Shannan Young; Alyssa McClelland; Bessie O'Connor; Sheri Zidenberg-Cherr; Debbie Fetter; Rachel Scherr (Journal of Nutrition Education and Behavior, 2023)

Hormone receptor activities of complex mixtures of known and suspect chemicals in personal silicone wristband samplers worn in office buildings - Anna S. Young; Nicholas Herkert; Heather M. Stapleton; Brent A. Coull; Russ Hauser; Thomas Zoeller; Peter A. Behnisch; Emiel Felzel; Abraham Brouwer; Joseph G. Allen (Chemosphere, 2023)

Persistent autism-relevant behavioral phenotype and social neuropeptide alterations in female mice offspring induced by maternal transfer of PBDE congeners in the commercial mixture DE-71 - Elena V. Kozlova; Matthew C. Valdez; Maximillian E. Denys; Anthony E. Bishay; Julia M. Krum; Kayhon M. Rabbani; Valeria Carrillo; Gwendolyn M. Gonzalez; Gregory Lampel; Jasmin D. Tran; Brigitte M. Vazquez; Laura M. Anchondo; et al. (Archives of Toxicology, 2022)
Polybrominated diphenyl ethers (PBDEs) are ubiquitous persistent organic pollutants (POPs) that are known neuroendocrine disrupting chemicals with adverse neurodevelopmental effects. PBDEs may act as risk factors for autism spectrum disorders (ASD), characterized by abnormal psychosocial functioning, although direct evidence is currently lacking. Using a translational exposure model, we tested the hypothesis that maternal transfer of a commercial mixture of PBDEs, DE-71, produces ASD-relevant behavioral and neurochemical deficits in female offspring. C57Bl6/N mouse dams (F0) were exposed to DE-71 via oral administration of 0 (VEH/CON), 0.1 (L-DE-71) or 0.4 (H-DE-71) mg/kg bw/d from 3 wk prior to gestation through end of lactation. Mass spectrometry analysis indicated in utero and lactational transfer of PBDEs (in ppb) to F1 female offspring brain tissue at postnatal day (PND) 15 which was reduced by PND 110. Neurobehavioral testing of social novelty preference (SNP) and social recognition memory (SRM) revealed that adult L-DE-71 F1 offspring display deficient short- and long-term SRM, in the absence of reduced sociability, and increased repetitive behavior. These effects were concomitant with reduced olfactory discrimination of social odors. Additionally, L-DE-71 exposure also altered short-term novel object recognition memory but not anxiety or depressive-like behavior. Moreover, F1 L-DE-71 displayed downregulated mRNA transcripts for oxytocin ( Oxt ) in the bed nucleus of the stria terminalis (BNST) and supraoptic nucleus, and vasopressin ( Avp ) in the BNST and upregulated Avp1ar in BNST, and Oxtr in the paraventricular nucleus. Our work demonstrates that developmental PBDE exposure produces ASD-relevant neurochemical, olfactory processing and behavioral phenotypes that may result from early neurodevelopmental reprogramming within central social and memory networks.

Body size and digestive system shape resource selection by ungulates: A cross‐taxa test of the forage maturation hypothesis - Saeideh Esmaeili; Brett R. Jesmer; Shannon E. Albeke; Ellen O. Aikens; Kathryn A. Schoenecker; Sarah R. B. King; Briana Abrahms; Bayarbaatar Buuveibaatar; Jeffrey L. Beck; Randall B. Boone; Francesca Cagnacci; Simon Chamaillé‐Jammes; et al. (Ecology Letters, 2021)
The forage maturation hypothesis (FMH) states that energy intake for ungulates is maximised when forage biomass is at intermediate levels. Nevertheless, metabolic allometry and different digestive systems suggest that resource selection should vary across ungulate species. By combining GPS relocations with remotely sensed data on forage characteristics and surface water, we quantified the effect of body size and digestive system in determining movements of 30 populations of hindgut fermenters (equids) and ruminants across biomes. Selection for intermediate forage biomass was negatively related to body size, regardless of digestive system. Selection for proximity to surface water was stronger for equids relative to ruminants, regardless of body size. To be more generalisable, we suggest that the FMH explicitly incorporate contingencies in body size and digestive system, with small‐bodied ruminants selecting more strongly for potential energy intake, and hindgut fermenters selecting more strongly for surface water.

Assessment of the Applicability of Capsid-Integrity Assays for Detecting Infectious Norovirus Inactivated by Heat or UV Irradiation - David I. Walker; Lisa J. Cross; Tina A. Stapleton; Connaire L. Jenkins; David N. Lees; James A. Lowther (Food and Environmental Virology, 2019)

Use of F-Specific RNA Bacteriophage to Estimate Infectious Norovirus Levels in Oysters - J. A. Lowther; L. Cross; T. Stapleton; N. E. Gustar; D. I. Walker; M. Sills; S. Treagus; V. Pollington; D. N. Lees (Food and Environmental Virology, 2019)

SEASTAR: A Mission to Study Ocean Submesoscale Dynamics and Small-Scale Atmosphere-Ocean Processes in Coastal, Shelf and Polar Seas - Christine Gommenginger; Bertrand Chapron; Andy Hogg; Christian Buckingham; Baylor Fox-Kemper; Leif Eriksson; Francois Soulat; Clément Ubelmann; Francisco Ocampo-Torres; Bruno Buongiorno Nardelli; David Griffin; Paco Lopez-Dekker; et al. (Frontiers in Marine Science, 2019)

Effect of Gestational Age on Maternofetal Vascular Function Following Single Maternal Engineered Nanoparticle Exposure - S. B. Fournier; S. Kallontzi; L. Fabris; C. Love; P. A. Stapleton (Cardiovascular Toxicology, 2019)

Estimating the abundance of polar bears on Wrangel Island during late summer using high-resolution satellite imagery: a pilot study - Michelle A. LaRue; Seth Stapleton (Polar Biology, 2018)

Feasibility of using high‐resolution satellite imagery to assess vertebrate wildlife populations - Michelle A. LaRue; Seth Stapleton; Morgan Anderson (Conservation Biology, 2017)
Although remote sensing has been used for >40 years to learn about Earth, use of very high‐resolution satellite imagery (VHR) (

Metal Nanomaterial Toxicity Variations Within the Vascular System - Alaeddin B. Abukabda; Phoebe A. Stapleton; Timothy R. Nurkiewicz (Current Environmental Health Reports, 2016)

Lomustine Nanoparticles Enable Both Bone Marrow Sparing and High Brain Drug Levels – A Strategy for Brain Cancer Treatments - Funmilola A. Fisusi; Adeline Siew; Kar Wai Chooi; Omotunde Okubanjo; Natalie Garrett; Katerina Lalatsa; Dolores Serrano; Ian Summers; Julian Moger; Paul Stapleton; Ronit Satchi-Fainaro; Andreas G Schätzlein; et al. (Pharmaceutical Research, 2016)

Differential Gene Expression in Liver, Gill, and Olfactory Rosettes of Coho Salmon (Oncorhynchus kisutch) After Acclimation to Salinity - Lindley A. Maryoung; Ramon Lavado; Theo K. Bammler; Evan P. Gallagher; Patricia L. Stapleton; Richard P. Beyer; Federico M. Farin; Gary Hardiman; Daniel Schlenk (Marine Biotechnology, 2015)

Pulmonary Cerium Dioxide Nanoparticle Exposure Differentially Impairs Coronary and Mesenteric Arteriolar Reactivity - Valerie C. Minarchick; Phoebe A. Stapleton; Dale W. Porter; Michael G. Wolfarth; Engin Çiftyürek; Mark Barger; Edward M. Sabolsky; Timothy R. Nurkiewicz (Cardiovascular Toxicology, 2013)

Genotoxicity in Atlantic killifish (Fundulus heteroclitus) from a PAH-contaminated Superfund site on the Elizabeth River, Virginia - Dawoon Jung; Cole W. Matson; Leonard B. Collins; Geoff Laban; Heather M. Stapleton; John W. Bickham; James A. Swenberg; Richard T. Di Giulio (Ecotoxicology, 2011)

Variation in saliva cotinine as a function of self-reported attempts to reduce cigarette consumption - Jennifer A. Fidler; John A. Stapleton; Robert West (Psychopharmacology, 2011)

Creative Solution for Implementation of Experiential, Competency-Based Palliative Care Training for Internal Medicine Residents - Douglas D. Ross; Deborah W. Shpritz; Susan D. Wolfsthal; Ann B. Zimrin; Timothy J. Keay; Hong-Bin Fang; Carl A. Schuetz; Laura M. Stapleton; David E. Weissman (Journal of Cancer Education, 2011)

Obesity and genetics regulate microRNAs in islets, liver, and adipose of diabetic mice - Enpeng Zhao; Mark P. Keller; Mary E. Rabaglia; Angie T. Oler; Donnie S. Stapleton; Kathryn L. Schueler; Elias Chaibub Neto; Jee Young Moon; Ping Wang; I-Ming Wang; Pek Yee Lum; Irena Ivanovska; et al. (Mammalian Genome, 2009)

Non-monophyly of the woody bamboos (Bambuseae; Poaceae): a multi-gene region phylogenetic analysis of Bambusoideae s.s. - Sarawood Sungkaew; Chris M. A. Stapleton; Nicolas Salamin; Trevor R. Hodkinson (Journal of Plant Research, 2009)

Phuphanochloa, a new bamboo genus (Poaceae: Bambusoideae) from Thailand - Sarawood Sungkaew; Atchara Teerawatananon; John A. N. Parnell; Chris M. A. Stapleton; Trevor R. Hodkinson (Kew Bulletin, 2008)

Effects of temperature variation on suicide in five U.S. counties, 1991–2001 - P. G. Dixon; A. N. McDonald; K. N. Scheitlin; J. E. Stapleton; J. S. Allen; W. M. Carter; M. R. Holley; D. D. Inman; J. B. Roberts (International Journal of Biometeorology, 2007)

Repeatability of extra‐pair mating in tree swallows - LINDA A. WHITTINGHAM; PETER O. DUNN; MARY K. STAPLETON (Molecular Ecology, 2006)
Models of sexual selection assume that female mating preferences are heritable and, thus, repeatable for individual females across multiple mating episodes. Previous studies of the repeatability of female preference have examined individuals in captivity and focused presumably on social mate choice. However, extra‐pair mating is widespread and can also influence sexual selection. We examined the repeatability of extra‐pair mating in a wild population of tree swallows ( Tachycineta bicolor ) by experimentally inducing females to lay two clutches in rapid succession within the same season. We found that the proportion of extra‐pair young and the number of extra‐pair sires were highly repeatable for individual females. However, the repeatability of specific extra‐pair sires was low. We suggest that this unusual pattern of mating may be due to females maximizing the heterozygosity of their offspring.

Irradiance-induced changes in the photobiology of Halophila johnsonii - J. I. Kunzelman; M. J. Durako; W. J. Kenworthy; A. Stapleton; J. L. C. Wright (Marine Biology, 2005)

The fate of 15 N added to high Arctic tundra to mimic increased inputs of atmospheric nitrogen released from a melting snowpack - A. M. Tye; S. D. Young; N. M. J. Crout; H. M. West; L. M. Stapleton; P. R. Poulton; J. Laybourn‐Parry (Global Change Biology, 2005)
Increases in the long‐range aerial transport of reactive N species from low to high latitudes will lead to increased accumulation in the Arctic snowpack, followed by release during the early summer thaw. We followed the release of simulated snowpack N, and its subsequent fate over three growing seasons, on two contrasting high Arctic tundra types on Spitsbergen (79°N). Applications of 15 N (99 atom%) at 0.1 and 0.5 g N m −2 were made immediately after snowmelt in 2001 as either Na 15 NO 3 or 15 NH 4 Cl. These applications are approximately 1 × and 5 × the yearly atmospheric deposition rates. The vegetation at the principal experimental site was dominated by bryophytes and Salix polaris while at the second site, vegetation included bryophytes, graminoids and lichens. Audits of the applied 15 N were undertaken, over two or three growing seasons, by determining the amounts of labeled N in the soil (0–3 and 3–10 cm), soil microbial biomass and different vegetation fractions. Initial partitioning of the 15 N at the first sampling time showed that ∼60% of the applied 15 N was recovered in soil, litter and plants, regardless of N form or application rate, indicating that rapid immobilization into organic forms had occurred at both sites. Substantial incorporation of the 15 N was found in the microbial biomass in the humus layer and in the bryophyte and lichen fractions. After initial partitioning there appeared to be little change in the total 15 N recovered over the following two or three seasons in each of the sampled fractions, indicating highly conservative N retention. The most obvious transfer of 15 N, following assimilation, was from the microbial biomass into stable forms of humus, with an apparent half‐life of just over 1 year. At the principal site the microbial biomass and vascular plants were found to immobilize the greatest proportion of 15 N compared with their total N concentration. In the more diverse tundra of the second site, lichen species and graminoids competed effectively for 15 NH 4 ‐N and 15 NO 3 ‐N, respectively. Results suggest that Arctic tundra habitats have a considerable capacity to immobilize additional inorganic N released from the snow pack. However, with 40% of the applied 15 N apparently lost there is potential for N enrichment in the surrounding fjordal systems during the spring thaw.

Sedimentary Nonylphenol Contamination in an Urbanized, Industrialized Segment of the Delaware River Estuary, USA - J. T. F. Ashley; A. Moore; H. M. Stapleton; D. J. Velinsky; M. P. Wilhelm (Bulletin of Environmental Contamination and Toxicology, 2003)

Abstracts of presentations on selected topics at the xlvth international plant protection congress (IPPC) July 25–30, 1999 - G. Theodoridis; D. Shaner; J. Townson; J. Kemp; P. Cory; D. Bartlett; P. Sutton; D. Collins; R. Wiehert; S. O. Duke; F. E. Dayan; J. G. Romagni; et al. (Phytoparasitica, 2000)

Nicotine availability from Eclipse tobacco-heating cigarette - J. A. Stapleton; Michael A. H. Russell; Gay Sutherland; Colin Feyerabend (Psychopharmacology, 1998)

Improvement of soil solarization with volatile compounds generated from organic Amendments - A. Gamliel; J. J. Stapleton (Phytoparasitica, 1997)